Millisecond-Response Nematic Liquid Crystal for Augmented Reality Displays - Jiaxing Tang; Ran Chen; Zhongwei An; Xinbing Chen; Pei Chen (Photonics, 2023)
Developing fast-response liquid crystals (LCs) is an essential way to achieve low cost, high resolution, and good visual experience for augmented reality (AR) displays. In this paper, we optimized one new nematic LC mixture SNUP01 to meet the requirements of fast-response phase-only liquid crystal on silicon (LCoS) devices in AR displays. The photoelectric performance of this new LC mixture and three commercial LC mixtures were further comparatively evaluated, and the 2π phase-change response speed of this new LC mixture was extrapolated. The research results indicate that SNUP01 possesses high birefringence, moderate dielectric anisotropy, low viscoelastic coefficient, low activation energy, and high figure of merit values. When using this LC mixture at 25 °C @ λ = 633 nm, a 2π phase change can be achieved at 5 V with a total response time of up to millisecond response. Widespread applications of this LC mixture for AR displays are foreseeable.